A study on the tensile properties of silicone rubber/polypropylene fibers/silica hybrid nanocomposites. (April 2016) - Ziraki, Sahar; Zebarjad, Seyed Mojtaba; Hadianfard, Mohammad Jafar
Abstract: Metacarpophalangeal joint implants have been usually made of silicone rubber. In the current study, silica nano particles and polypropylene fibers were added to silicone rubber to improve silicone properties. The effect of the addition of silica nano particles and polypropylene fibers on the tensile behavior of the resultant composites were investigated. Composite samples with different content of PP fibers and Silica nano particles (i. e. 0, 1 and 2 wt%) as well as the hybrid composite of silicone rubber with 1 wt% SiO2 and 1 wt% PP fiber were prepared. Tensile tests were done at constant cross head speed. To study the body fluid effect on the mechanical properties of silicone rubber composites, samples soaked in simulated body fluid (SBF) at 37 °C were also tested. The morphology of the samples were studied by scanning electron microscope. Results of analysis revealed that an increase in PP fibers and silica nano particles content to 2 wt%, increases the tensile strength of silicone rubber of about 75% and 42% respectively. It was found out that the strength of the samples decreases after being soaked in simulated body fluid, though composites with PP fibers as the reinforcement showed less property degradation.